A practical guide to designing phase II trials in oncology - Brown, Sarah R.; Gregory, Walter M.; Twelves, Chris; Brown, Julia (Julia M.) (Chichester, West Sussex : John Wiley & Sons Inc., 2014)
"Choosing Your Phase II Trial Design provides an overview to clinical trial researchers of the steps involved in designing a phase II trial and provides a way to identify a range of optimal designs. Providing a practical guide containing the information needed to make crucial decisions regarding phase II trial designs, it sets forth specific points for consideration between the statistician and clinician when designing a phase II trial, including issues such as how the treatment works, choice of outcome measure and randomisation. A detailed library of trial designs is featured along with examples and case studies accompanied by illustrations using a flow diagram, highlighting the choices made for each key point throughout the process. For those new to trial design, the book provides an introduction to the concepts behind informed decision making in phase II trials, offering a unique and practical learning tool. For those familiar with phase II trial design, the reader will benefit from exposure to new, less familiar trial designs, providing alternative options to those which the reader may not have previously used"--Provided by publisher.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Clinical Trials, Phase II as Topic; Antineoplastic Agents -- therapeutic use; Drug Evaluation -- methods; Neoplasms -- drug therapy; Clinical trials; Antineoplastic agents -- Therapeutic use; Tumors -- Treatment; HEALTH & FITNESS -- Diseases -- General; MEDICAL -- Clinical Medicine; MEDICAL -- Diseases; MEDICAL -- Evidence-Based Medicine; MEDICAL -- Internal Medicine; Antineoplastic agents -- Therapeutic use; Clinical trials; Tumors -- Treatment; Clinical Trials, Phase II as Topic; Electronic books; Electronic books